Plasmodium falciparum glycolipid synthesis: constant and variant molecules of isolates and of strains with differing knob and cytoadherence phenotype. - Sherwood, J; Spitalnik, S; Suarez, S; Marsh, K; Howard, R (1988)
Plasmodium falciparum-infected erythrocytes were metabolically labeled with tritiated glucosamine. Lipid extracts were analyzed by high-performance thin-layer chromatography to compare labeled molecules of eleven isolates from patients, six cytoadherent in vitro strains, and two knobbed and two knobless strains from Aotus monkeys. Up to nineteen labeled bands were identified. Glycolipid GL1, previously identified in Malayan Camp, was present in all isolates and strains. Other molecules, between CG and GM1 and between GM1 and GD1a, varied in mobility or presence. There was no apparent association between labeled molecules and the presence of knobs or the property of cytoadherence.